Performance, blood chemistry and serum electrolytes of broilers given water from different sources (2018)
The role of water sources in broiler performance was assessed using 168 Abor Acre broiler birds. The birds were randomly allotted to 4 treatments (Treatment 1(T1) - tap water, Treatment 2 (T2) – bore-hole water, Treatment 3 (T3) – well water and Treatment 4 (T4) – river water), with 6 replicates each in a completely randomized design. The initial weight was measured at hatch and subsequently on weekly basis till the final week of study. Feed intake and conversion ratio were recorded and computed, while rectal temperature was obtained using a clinical thermometer inserted into the rectum of the broiler chicken. On day 42, blood was collected via the jugular vein into sample bottles for hematological and serum electrolyte assay. Data obtained were analyzed and means separated using Duncan Multiple Range Test (DMRT). Water source was observed to significantly influence rectal temperature at the 4th week, with birds served borehole water having higher rectal temperature than birds served river water. Source of water offered to the birds was also observed to influence (p<0.05) serum levels of sodium, calcium, potassium and phosphorus. Sodium level was significantly higher in birds offered river water, while borehole water resulted in significantly higher phosphorus level in broiler chicken.